Advancements and Implications of Product Service Systems in the Automobile Industry: A Comprehensive Review - Dolly Sharma; Vinod Yadav; Dalip Singh (Engineering Proceedings)
This research paper explains how, in the last twenty years, the study and research of product service systems (PSSs) in the automobile sphere has experienced high growth due to its unique approach in enriching customer value and experience, strengthening product competence for both customers and providers, and facilitating improved control and management over the product lifecycle. The review of the literature for the automobile sphere is classified into four categories: (i) numbers of publications per year, (ii) journal-specific publications, (iii) year-wise publications, and (iv) growth of research based on applied techniques. The integration of additional services proves instrumental in improving product design, optimizing operations, and offering innovative new services. Additionally, this paper explains how the product service system (PSS) plays an important role in enriching outcomes from customers, efficiency of the product, and lifecycle management. Its future scope lies in integration and fostering innovative ideas, improved customer service, and performance-based contracts because PSSs can drive long-term relationships, trust, and growth in the industry. The paper emphasizes the importance of user-centered design and innovative business models. The primary objective of this review paper is to provide a comprehensive analysis of product service systems (PSSs) in the automobile industry, focusing on progress, challenges, and opportunities, with the aim of responding to the evolution of consumer behavior through innovative innovations such as digitalization and sustainability integration.